2019 IEEE 30th International Symposium on Software Reliability Engineering (ISSRE) 2019
DOI: 10.1109/issre.2019.00046
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Data Preparation on the Fairness of Software Systems

Abstract: Machine learning models are widely adopted in scenarios that directly affect people. The development of software systems based on these models raises societal and legal concerns, as their decisions may lead to the unfair treatment of individuals based on attributes like race or gender. Data preparation is key in any machine learning pipeline, but its effect on fairness is yet to be studied in detail. In this paper, we evaluate how the fairness and effectiveness of the learned models are affected by the removal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…For example, Zhang and Harman [78] investigated potential influencing factors of software fairness and found that enlarging the feature set was a possible way to improve fairness. Valentim et al [70] and Biswas and Rajan [26] explored the impact of different pre-processing techniques on fairness and derived insights for choosing appropriate techniques to improve software fairness.…”
Section: Related Workmentioning
confidence: 99%
“…For example, Zhang and Harman [78] investigated potential influencing factors of software fairness and found that enlarging the feature set was a possible way to improve fairness. Valentim et al [70] and Biswas and Rajan [26] explored the impact of different pre-processing techniques on fairness and derived insights for choosing appropriate techniques to improve software fairness.…”
Section: Related Workmentioning
confidence: 99%
“…It is a common practice in ML software to include data processing stages to manipulate and transform the training data for the downstream learning tasks. Biswas and Rajan [45] and Valentim et al [151] tested whether data processing methods introduce fairness bugs using causal reasoning. Specifically, they employed each commonly-used data processing method as an intervention into the development process of ML software and kept other settings unchanged.…”
Section: Algorithm Testingmentioning
confidence: 99%
“…Our work takes inspiration from earlier empirical studies and comparisons of fairness techniques [6,13,17,23,27,28,31], which help practitioners and researchers better understand the state of the art. But unlike these works, we experiment with ensembles and with fairness stability.…”
Section: Related Workmentioning
confidence: 99%